2003
DOI: 10.1111/j.1749-0774.2003.tb00158.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase GSTM1, GSTT1 and p53 Codon 72 Polymorphisms in Human Tumor Cells

Abstract: The genes of the glutathione S-transferase (GST) family encode enzymes that appear to be critical in cellular protection against the cytotoxic effects, whereas p53 is a tumor suppressor gene. Despite a large number of studies on germline polymorphisms of GSTM1, GSTT1 and p53 genes, there have been very few reports on genotyping of these genes in human malignant tumor cells. In this study, we investigated GSTM1, GSTT1 and p53 codon 72 polymorphisms in a variety of human tumor cell lines originating from differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 22 publications
0
27
0
2
Order By: Relevance
“…The genes for both GSTM1 and GSTT1 isoforms could exhibit an insertion/deletion polymorphism null alleles/ genotypes resulting in loss of enzymatic activity which was associated with a number of malignancies including cervical neoplasia (12)(13)(14). Previous reports have associated GST M1 and T1 null genotype with an enhanced risk of precancerous lesions or cervical cancer (15,16), but still, other studies have not confirmed this correlation (12). Considering that null alleles of GSTM1 and GSTT1 genes could be used as potential molecular markers in cervical cancer prevention, further large studies and adequate meta-analyses are needed to confirm and validate this hypothesis.…”
Section: Genetic Polymorphisms Of Glutathione S Transferase and Cervimentioning
confidence: 99%
See 1 more Smart Citation
“…The genes for both GSTM1 and GSTT1 isoforms could exhibit an insertion/deletion polymorphism null alleles/ genotypes resulting in loss of enzymatic activity which was associated with a number of malignancies including cervical neoplasia (12)(13)(14). Previous reports have associated GST M1 and T1 null genotype with an enhanced risk of precancerous lesions or cervical cancer (15,16), but still, other studies have not confirmed this correlation (12). Considering that null alleles of GSTM1 and GSTT1 genes could be used as potential molecular markers in cervical cancer prevention, further large studies and adequate meta-analyses are needed to confirm and validate this hypothesis.…”
Section: Genetic Polymorphisms Of Glutathione S Transferase and Cervimentioning
confidence: 99%
“…The glutathione S-transferases (GSTs) represent an important class of detoxifying enzymes belonging to phase II detoxification enzymes superfamily, which protect cells against endogenous and exogenous molecular injury inducing compounds including mutagens, carcinogens and other toxic chemicals, thus playing a crucial role in the detoxification process (11). The genes for both GSTM1 and GSTT1 isoforms could exhibit an insertion/deletion polymorphism null alleles/ genotypes resulting in loss of enzymatic activity which was associated with a number of malignancies including cervical neoplasia (12)(13)(14).…”
Section: Genetic Polymorphisms Of Glutathione S Transferase and Cervimentioning
confidence: 99%
“…The role of genetic factors in development of ovarian cancer has not been explored. According to earlier studies, genetic polymorphism in cell cycle regulatory and pro-apoptotic genes leads to cancer development [7,8]. Prevalence of BRCA mutation in sporadic ovarian cancer has been found very less and no change has been found in p53 mutation frequencies between BRCA-associated and sporadic ovarian cancer [9,10].…”
Section: Introductionmentioning
confidence: 97%
“…Os compostos eletrofílicos, tanto endógenos como exógenos, estão constantemente em contato com nossas células e são agentes potencialmente mutagênicos por reagirem sobre a cadeia de DNA provocando modificação de sua estrutura. As enzimas do Glutation-S-Transferase têm um importante papel na carcinogênese dos tumores humanos porque estão envolvidas na neutralização e detoxificação de uma variedade desses compostos, tanto derivados do próprio metabolismo celular, como de substâncias produzidas por indústrias químicas, incluindo metileno clorídrico, etileno, brometo de etídeo, óxido etileno, e 1,3-butadieno [5][6][7][8] . Atualmente seis classes de GST's são conhecidas: alpha, mu, pi, theta, omega e zeta 1 .…”
Section: Introductionunclassified
“…Na glândula tireoide esse risco aumenta em 2,6 vezes 1,5,6,8,12,13 . Sendo o GST um fator de proteção do DNA da célula, os pacientes com genótipo nulo para esse sistema não possuem essa proteção e, consequentemente, estão mais propensos ao desenvolvimento de diversos tumores [5][6][7][8][12][13][14][15][16][17][18][19] . As células cancerosas possuem habilidade de superexpressar determinados genes a fim de adquirir qualidades que permitam sua multiplicação descontrolada.…”
Section: Introductionunclassified